Factors Associated With The Choice Of Place For Delivery Assistance To Pregnant Women In The Third Trimester - Maria Susanti; Ani Kristianingsih; Neng Nurhickmah; Maya Dwi Lestari; Fitraluki Haning; Indah Lestari; Eka Safitri; Dwi Wahyuni (Journal of Applied Nursing and Health, 2022)
Background: The low coverage of deliveries in health facilities is 64.66% of the 100% target in 2020, one of which is caused by the lack of knowledge of pregnant women about the importance of giving birth in health facilities. This study aimed to determine the factors associated with the choice of place for delivery assistance to pregnant women in the third trimester in the working area of the Public Health Center  Bengkunat Belimbing In 2021. Method: This research design is a descriptive non-experimental, correlational research with a cross-sectional method. The population in this study were all third-trimester pregnancies in November 2021, with 32 pregnant women. The sample amounted to 32 respondents, third trimester of pregnant women taken from the population using the Total Sampling technique. Bivariate analysis in this study used the chi-square test with an alpha value (α) of 0.01. Result: The research result obtained values for each research variable, including mother's knowledge with a p-value of 0.000, mother's behavior with a p-value of 0.000, and distance to health care facilities with a p-value of 0.006. Conclusion: From the results of this study, the researchers suggest optimizing the intervention of problems related to factors related to the choice of place for delivery assistance, namely increasing health education about the importance of giving birth in health facilities to mothers and families, optimizing the use of the Birth Waiting House (RTK) and proposing to the village or local governments in the construction of health service facilities, especially in remote areas.